2021
DOI: 10.1038/s41586-021-04246-z
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting SWI/SNF ATPases in enhancer-addicted prostate cancer

Abstract: The switch/sucrose non-fermentable (SWI/SNF) complex has a crucial role in chromatin remodelling1 and is altered in over 20% of cancers2,3. Here we developed a proteolysis-targeting chimera (PROTAC) degrader of the SWI/SNF ATPase subunits, SMARCA2 and SMARCA4, called AU-15330. Androgen receptor (AR)+ forkhead box A1 (FOXA1)+ prostate cancer cells are exquisitely sensitive to dual SMARCA2 and SMARCA4 degradation relative to normal and other cancer cell lines. SWI/SNF ATPase degradation rapidly compacts cis-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
169
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(185 citation statements)
references
References 51 publications
15
169
0
1
Order By: Relevance
“…And ACBI1 treatment only impacted cell growth of cancer cell lines known to depend on BRG1/BRM function—an effect that could be blocked by addition of a competing bromodomain ligand—demonstrating notable specificity and selectivity in the action of ACBI1 [ 16 ]. Subsequent analyses using this commercially available degrader as both a biological tool compound [ 18 ] and small molecule therapeutic [ 17 ] have been reported, expanding the use of this selective degrader as a means to inactivate SWI/SNF function rapidly. This well-characterized molecule was key to uncovering the novel findings in this study as chemical degradation of BRG1 allowed for analysis of rSWI/SNF function at much earlier timepoints than previously used when targeting rSWI/SNF [ 5 , 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…And ACBI1 treatment only impacted cell growth of cancer cell lines known to depend on BRG1/BRM function—an effect that could be blocked by addition of a competing bromodomain ligand—demonstrating notable specificity and selectivity in the action of ACBI1 [ 16 ]. Subsequent analyses using this commercially available degrader as both a biological tool compound [ 18 ] and small molecule therapeutic [ 17 ] have been reported, expanding the use of this selective degrader as a means to inactivate SWI/SNF function rapidly. This well-characterized molecule was key to uncovering the novel findings in this study as chemical degradation of BRG1 allowed for analysis of rSWI/SNF function at much earlier timepoints than previously used when targeting rSWI/SNF [ 5 , 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…BAF (SWI/SNF) chromatin remodelling complexes play critical roles in cancer 23,24 . For example, it has recently been shown that androgen receptor (AR) and forkhead box A1 (FOXA1) expressing prostate cancer cells are sensitive to simultaneous degradation of BAF complex subunits SMARCA2, SMARCA4 and PBRM1 25 . The synthetic lethality between SMARCA2 and SMARCA4, resulting in sensitivity of SMARCA4-deficient cells to loss of SMARCA2, has been discovered and validated by genetic methods [5][6][7] , but pharmacological validation and exploitation of this synthetic lethal relationship has been hampered by the lack of suitably selective small molecules, in particular for effective in vivo use in animal models 10,20 .…”
Section: Discussionmentioning
confidence: 99%
“…While it cannot entirely be excluded that more efficacious degraders may cause stronger effects, it is also possible that cells can more readily adapt to loss of SMARCA2 and SMARCA4 in vivo than in vitro, highlighting the need for in vivo validation of therapeutic concepts. The possibility that other indications such as prostate cancer or multiple myeloma are more dependent dual loss of SMARCA2 and SMARCA4 remains 25 . In either case, appropriate drug combinations could enhance in vivo efficacy and warrant dedicated investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This was applied to target BRD9, a SWI/SNF complex subunit [ 33 ]. For example, AU-15330 induced a potent inhibitor of tumor growth in xenograft models of prostate cancer, and synergized with the androgen receptor antagonist enzalutamide, even inducing disease remission in castration-resistant prostate cancer models without toxicity [ 60 ].…”
Section: Preclinical Data and Relevant Clinical Datamentioning
confidence: 99%
“… Immunologic and genomic hallmarks of DEC. ( A ) DEC is not amenable to hormone therapy owing to its loss of ER and PR [ 5 , 6 ]. ( B ) Mutations in genes encoding subunits of the SWI/SNF chromatin remodeling complex could be targeted by small-molecule allosteric inhibitors and proteolysis-targeting chimeras (PROTACs) [ 29 , 60 ]. ( C , D ) Defects in MMR and the increased expression of PDL1 could be a target for immune checkpoint inhibitors [ 8 , 29 , 69 , 72 ].…”
Section: Figurementioning
confidence: 99%